If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7c + -3 = 6c + 4 Reorder the terms: -3 + 7c = 6c + 4 Reorder the terms: -3 + 7c = 4 + 6c Solving -3 + 7c = 4 + 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. -3 + 7c + -6c = 4 + 6c + -6c Combine like terms: 7c + -6c = 1c -3 + 1c = 4 + 6c + -6c Combine like terms: 6c + -6c = 0 -3 + 1c = 4 + 0 -3 + 1c = 4 Add '3' to each side of the equation. -3 + 3 + 1c = 4 + 3 Combine like terms: -3 + 3 = 0 0 + 1c = 4 + 3 1c = 4 + 3 Combine like terms: 4 + 3 = 7 1c = 7 Divide each side by '1'. c = 7 Simplifying c = 7
| z^6+-2z^3+2=0 | | 52-3d=22 | | 4x+33=13-66 | | (2x-15)=90 | | (3x+5)=90 | | 8z-5=19 | | x=-38 | | X^2-3y^2+2x*y+4x-8*y-5=0 | | 3=2x(4x^2+1) | | 3x+2(11+3)=x-12+2+x | | 2(z-2)=8 | | 3cos^3(x)-3cos(x)=0 | | 5(19-x)=3(3x-1) | | (6d-3)+(2d+6)+d= | | 16=3(4+2x) | | 40x+90(40-x)=2345 | | 15=3(2x+3) | | 3(2+x)=15 | | 20x^2+100x=125 | | 2x-11=-21 | | 5x+2y=96 | | (x/8)+(x/5)=13 | | 6(X-3)=7(X-1) | | 6x-15=4+8x | | 4*x-1-3*2x+3-1=0 | | 4(3z-1)=0 | | 6x-15=4+8 | | 48=0-8x | | 0-3x=15 | | tan(6x)=k | | 5(2x+3)=47 | | 2x+4-5x=3x-6-x*(5/x) |